How AI Helps Second Language Learners Acquire Target Language: An Analysis from a Cross-Cultural Perspective - Xiang, Chenzhe (Transactions on Social Science, Education and Humanities Research, 2024)
With the development of science and technology, artificial intelligence is gradually being applied in various fields. In the field of second language acquisition, AI, as an auxiliary tool, can effectively help learners acquire the target language. Language learning not only includes linguistic knowledge, but also the culture of the target language. This paper analyzes the advantages of AI in L2 acquisition from a cross-cultural perspective. By providing examples to illustrate the application of AI in second language acquisition and analyzing the unique advantages of AI from a cross-cultural perspective, the author found that AI can promote L2 acquisition in terms of cross-cultural content, cross-cultural functions, and the creation of cross-cultural environment. L2 learners should make appropriate use of the advantages of AI in cross-cultural perspectives to narrow the social distance to the target language, thus they can better acquire a second language. However, learners should also be aware of the potential risks of AI technology and engage more in real-life scenarios for communication.